Creating the evidence: lessons from cochlear implants. - Fabry D (Journal of the American Academy of Audiology)
This paper compares the evidence-based outcomes between cochlear implants and hearing aids during the past several decades. Despite many similarities, there are also some important differences that define the progress for the two disciplines. Perhaps the most significant distinction exists in terms of the difference between the Food and Drug Administration's treatment of hearing aids as Class I medical devices, while cochlear implants are defined as Class III devices. Another point of divergence has been the number of publications in archival, peer-reviewed journals; implant papers have been steadily increasing during the past decade, while hearing aid papers have declined during the same period. The impact of these differences on the past, present, and future of hearing aid and cochlear implant research, technology, and clinical practice is discussed.